Hypocholesterolemia - Moutzouri, Elisavet; Elisaf, Moses; N. Liberopoulos, Evangelos (Current Vascular Pharmacology, 2011)
Hypocholesterolemia is defined as total cholesterol (TC) and low density lipoprotein cholesterol (LDL-C) levels below the 5th percentile of the general population adjusted for age, gender and race. Hypocholesterolemia may be attributed to inherited disorders or several secondary causes. Inherited forms of hypocholesterolemia consist of a group of rare diseases. The best studied are familial hypobetalipoproteinemia (FHBL) and abetalipoproteinemia (ABL). Clinical diagnosis rests on lipid levels and the pattern of inheritance after secondary causes are excluded. Patients with primary hypobetalipoproteinemias may manifest a variety of symptoms and signs affecting several organs (steatorrhea, neurological and ophthalmological symptoms, non-alcoholic fatty liver disease) or be asymptomatic. Understanding hypocholesterolemia and the underlying molecular basis is of crucial importance since this may provide new insights in the treatment of hypercholesterolemia and cardiovascular disease.
Keywords: low cholesterol